MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 3-4 TAHUN DENGAN METODE BERCERITA DENGAN BONEKA JARI DI PAUD AQILA CERIA JALAN PURNAMA PERUM PURNAMA INDAH BLOK A6 NO 4 DESA PANDAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Nurhanipa, Nurhanipa; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Background problem in this study is the lack of a child's ability to say with a clear vocabulary, vocabulary of children are still little, the child may not be able to tell his experience, some children are less able to repeat the stories and storytelling with finger has not been implemented in PAUD Aqila Ceria. The formulation in this study is whether to use storytelling with finger puppets can enhance children's ability to speak at the age of 3 to 4 years. This study aims to find out how high the increase in children's ability to talk after using storytelling with puppets finger. The research method is a method of classroom action research conducted in two cycles, each cycle consisting of several stages: planning, action, observation and reflection. The number of subjects in this study were 4 boys and 11 girls. Data taken from the results of the evaluation at the end of each cycle. The study involved a group of friends or colleagues in other regions as observers. Based on data obtained from the results of the percentage increase in the first cycle is 46.85% with 37.10% and increased in the second cycle is 68.33% with a 45.8% increase. Therefore it can be concluded that the method of storytelling with finger puppets can enhance children's ability to speak at the age of 3 to 4 years old in PAUD Aqila Ceria.Keywords: Speech, The Story, Finger Puppets